ENFAT-AODV: the fault-tolerant routing protocol for high failure rate Wireless Sensor Networks - Che-Aron, Zamree; Mohammed Al-Khateeb, Wajdi Fawzi; Anwar, Farhat (2010)
As more and more real Wireless Sensor Network's (WSN) applications have been tested and deployed over the last decade, the research community of WSN realizes that several issues need to be revisited from practical angles, such as reliability and availability. Furthermore, fault-tolerance is one of the main issues in WSNs since it becomes critical in real deployed environments where network stability and reduced inaccessibility times are important. Basically, wireless sensor networks suffer from resource limitations, high failure rates and faults caused by the defective nature of wireless communication and the wireless sensor itself. This can lead to situations, where nodes are often interrupted during data transmission and blind spots occur in the network by isolating some of the devices. In this paper, we address the reliability issue by designing an enhanced fault-tolerant mechanism for Ad hoc On-Demand Distance Vector (AODV) routing protocol used in WSN called the ENhancement of FAult-Tolerant AODV (ENFAT-AODV) routing protocol. We design and implement a backup route scheme by creating a backup path for every node in the network. When a node gets failure to deliver the data packet through the main route, it immediately employs the backup route to become a new main path for the next data packet delivery to reduce a number of data packets dropped and to maintain the continuity of data packet transmission in presence of some faults (node or link failures). Furthermore, with high failure rate, this proposed routing protocol improves the throughput and the average End-to-End delay and decrease the control packet load in the network. Consequently, the reliability, availability and maintainability of the network are achieved. The simulation shows that proposed routing scheme is better than the AODV routing.